Programa De Entrenamiento Deportivo En Futbol Para Fomentar La Formación Deportiva De Los Jóvenes De La Escuela Armenia Fútbol Club (2014)
This project shows the process done with 25 young’s who were Amory 16 and 18 years old. They are from the juvenile and pre juvenile category of the Armenia football Club school, where it was created the sports training program. Initially, the classes were planed so that they had a coherent sequence. Besides, some data were collected to have an idea of the performance of each player. This intervention process is supported by the schedules and the lesson plans which were, elaborated with the purpose of giving compliments to the objectives proposed at the beginning of this project Finally, it is proposed to analyze the group process according to what her been proposed in the lesion plans, and this is established in the final objetivations. With this, it is pretended to show that there are many positive things when it is implemented a sport training program in Armenia Football Club School.